ORA59 and EIN3 interaction couples jasmonate‐ethylene synergistic action to antagonistic salicylic acid regulation of PDF expression. Issue 4 (April 2017) - He, Xiang; Jiang, Jishan; Wang, Chang‐Quan; Dehesh, Katayoon
Abstract: Hormonal crosstalk is central for tailoring plant responses to the nature of challenges encountered. The role of antagonism between the two major defense hormones, salicylic acid (SA) and jasmonic acid (JA), and modulation of this interplay by ethylene (ET) in favor of JA signaling pathway in plant stress responses is well recognized, but the underlying mechanism is not fully understood. Here, we show the opposing function of two transcription factors, ethylene insensitive3 (EIN3) and EIN3‐Like1 (EIL1), in SA‐mediated suppression and JA‐mediated activation of PLANT DEFENSIN1.2 ( PDF1.2 ). This functional duality is mediated via their effect on protein, not transcript levels of the PDF1.2 transcriptional activator octadecanoid‐responsive Arabidopsis 59 (ORA59). Specifically, JA induces ORA59 protein levels independently of EIN3/EIL1, whereas SA reduces the protein levels dependently of EIN3/EIL1. Co‐infiltration assays revealed nuclear co‐localization of ORA59 and EIN3, and split‐luciferase together with yeast‐two‐hybrid assays established their physical interaction. The functional ramification of the physical interaction is EIN3‐dependent degradation of ORA59 by the 26S proteasome. These findings allude to SA‐responsive reduction of ORA59 levels mediated by EIN3 binding to and targeting of ORA59 for degradation, thus nominating ORA59 pool as a coordination node for the antagonistic function of ET/JA and SA. Abstract : SA treatment promotes EIN3 binding and targeting to ORA59 for degradation, whereas JA promotes EIN3 transactivation of ORA59 and induction of PDF1.2 Thus ORA59 acts as a coordinating node for the antagonistic function of ET/JA and SA.